LINGUISTIC TENDENCIES OF ANOREXIA NERVOSA ON SOCIAL MEDIA USERS FACEBOOK (PRAGMATIC STUDY) - Wincana, Gita; Rahmat, Wahyudi; Tatalia, Ricci Gemarni (ppjbsip, 2022)
This research is motivated by the large number of facebook users who express their discomfort with body shape and after further review, the discomfort expressed is included in the characteristics of people who have a tendency to anorexia nervosa. This study was conducted to describe the linguistic tendency of anorexia nervosa on facebook social media users, especially on the